2018
DOI: 10.1097/hmr.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

How to make a job more than just a paycheck: Understanding physician disengagement

Abstract: To reduce physician disengagement, we recommend leadership development around key skills (i.e., visibility, transparency, accessibility). We also suggest that improving supervisors' (e.g., clinical service chiefs') knowledge about workflow processes, staffing needs, patient panel sizes, and administrative tasks carried by physicians could better balance physicians' workload. Finally, human resource systems can help reduce disengagement by adjusting hiring and training processes to mitigate low staffing levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Senior leadership teams, particularly Chief Executive Officers (CEO), manage physicians by nagging, arguing and reminding them of their responsibilities, that is, they fail to meaningfully engage medical leaders. 50 77 78 CEOs and senior leadership teams tend to crowd medical leaders’ agendas with numerous committees or ‘strategic’ meetings that are filled with operational, not strategic matters. 34 40 51 …”
Section: Resultsmentioning
confidence: 99%
“…Senior leadership teams, particularly Chief Executive Officers (CEO), manage physicians by nagging, arguing and reminding them of their responsibilities, that is, they fail to meaningfully engage medical leaders. 50 77 78 CEOs and senior leadership teams tend to crowd medical leaders’ agendas with numerous committees or ‘strategic’ meetings that are filled with operational, not strategic matters. 34 40 51 …”
Section: Resultsmentioning
confidence: 99%
“…they fail to meaningfully engage medical leaders. [43,64,65] CEOs and senior leadership teams tend to crowd medical leaders’ agendas with numerous committees or “strategic” meetings that are filled with operational, not strategic matters. [21,41,44]…”
Section: Resultsmentioning
confidence: 99%
“…Barriers and facilitators of psychological safety emerged at an individual level, with personality influencing team dynamics significantly. Whilst the literature reporting on healthcare teams highlights how the behaviour and personality of a leader specifically can be a barrier to psychological safety [4,[41][42][43], the impacts of dominating personalities amongst other team members is less explored. A shy personality was reported as a barrier, and whilst this may be viewed as an innate characteristic, the influence of the team in negating this should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…This enables focus on providing high quality care, as opposed to managing the expectations around voicing dissent and disagreement. It has also been shown that psychological safety increases physician engagement [ 4 ], reduces burnout [ 5 ] and promotes creativity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%